2006
DOI: 10.4049/jimmunol.177.12.8569
|View full text |Cite
|
Sign up to set email alerts
|

Functional Requirements for the Lysosomal Thiol Reductase GILT in MHC Class II-Restricted Antigen Processing

Abstract: Ag processing and presentation via MHC class II is essential for activation of CD4+ T lymphocytes. γ-IFN-inducible lysosomal thiol reductase (GILT) is present in the MHC class II loading compartment and has been shown to facilitate class II Ag processing and recall responses to Ags containing disulfide bonds such as hen egg lysozyme (HEL). Reduction of proteins within the MHC class II loading compartment is hypothesized to expose residues for class II binding and protease trimming. In vitro analysis has shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 31 publications
(53 reference statements)
5
57
0
Order By: Relevance
“…The LLO point mutation (G486D) in the DP-L4044 strain used in the current study resides in the cholesterol-binding domain of the toxin (45), suggesting the interesting possibility that DC phagosomes present a different composition or configuration of membrane cholesterol, reducing toxin binding. Alternatively, the access of L. monocytogenes to the active form of GILT, a host-derived thiol reductase involved in antigen processing (17) that recently has been shown to be required for the activation of LLO (40), may be restricted in early DC phagosomes. Finally, exposure to lowlevel, NOX2-generated reactive oxygen species immediately upon the arrival of L. monocytogenes into DC phagosomes could inactivate LLO, similarly to a scenario proposed for activated macrophages (28).…”
Section: Discussionmentioning
confidence: 99%
“…The LLO point mutation (G486D) in the DP-L4044 strain used in the current study resides in the cholesterol-binding domain of the toxin (45), suggesting the interesting possibility that DC phagosomes present a different composition or configuration of membrane cholesterol, reducing toxin binding. Alternatively, the access of L. monocytogenes to the active form of GILT, a host-derived thiol reductase involved in antigen processing (17) that recently has been shown to be required for the activation of LLO (40), may be restricted in early DC phagosomes. Finally, exposure to lowlevel, NOX2-generated reactive oxygen species immediately upon the arrival of L. monocytogenes into DC phagosomes could inactivate LLO, similarly to a scenario proposed for activated macrophages (28).…”
Section: Discussionmentioning
confidence: 99%
“…Mutational analyses have demonstrated that Cys-222 is responsible for disulfide-mediated dimerization of secreted precursor GILT (45). Mutations of Cys-91, -98, -200, or -211 impair processing to the mature form (23,45). Remarkably, although Cys-211 is present in the C-terminal pro-peptide and presumably nonessential to the function of the mature form, C211S GILT and a mutant in its proposed disulfide partner, C200S GILT, are impaired in processing to the mature form, although the mutant precursors remain active especially at neutral pH (45).…”
Section: Hastings and Cresswellmentioning
confidence: 99%
“…Such proteins should present special characteristics: the redox center of the Arabidopsis NTRs is situated in a groove and is only accessible to proteins with a disulfide bridge on the surface of a small molecule or on an appendage of a large molecule (Dai et al, 1996). To date, such structures have been described only for the thioredoxin superfamily and, more recently, for the g-interferon-inducible thiol reductases (Hastings et al, 2006), with six homologs in the Arabidopsis genome, one of them implicated in high O-acetyl-LSer accumulation (Ohkama-Ohtsu et al, 2004).…”
Section: A Glutathione-dependent Pathway Reduces Type H Thioredoxins mentioning
confidence: 99%